Regulation of Adipocyte Formation by GLP-1/GLP-1R Signaling - Challa, Tenagne Delessa (American Society for Biochemistry and Molecular Biology, 2012)
Increased nutrient intake leads to excessive adipose tissue accumulation, obesity, and the development of associated metabolic disorders. How the intestine signals to adipose tissue to adapt to increased nutrient intake, however, is still not completely understood. We show here, that the gut peptide GLP-1 or its long-lasting analog liraglutide, function as intestinally derived signals to induce adipocyte formation, both in vitro and in vivo. GLP-1 and liraglutide activate the GLP-1R, thereby promoting pre-adipocyte proliferation and inhibition of apoptosis. This is achieved at least partly through activation of ERK, PKC, and AKT signaling pathways. In contrast, loss of GLP-1R expression causes reduction in adipogenesis, through induction of apoptosis in pre-adipocytes, by inhibition of the above mentioned pathways. Because GLP-1 and liraglutide are used for the treatment of type 2 diabetes, these findings implicate GLP-1 as a regulator of adipogenesis, which could be an alternate pathway leading to improved lipid homeostasis and controlled downstream insulin signaling.